1997
DOI: 10.1046/j.1365-2036.1997.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of oral 5‐aminosalicylic acid for the prevention of early relapse in Crohn's disease

Abstract: Background Recent data indicate that 5‐aminosalicylic acid (5‐ASA) is most effective in preventing relapse of Crohn's disease in patients with a short duration of remission before enrolment. Aim To evaluate the efficacy of oral 5‐ASA treatment, started immediately after achieving steroid‐induced remission, in preventing clinical relapses of Crohn's disease. Methods Patients with active Crohn's disease, achieving remission on steroids, were randomized to oral 5‐ASA 3 g/day or placebo, while steroids were tapere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 9 publications
0
29
0
1
Order By: Relevance
“…8 However, de Franchis and coworkers showed that once patients achieved disease remission on mesalamine, less than 50% of patients were able to sustain disease remission after one year of maintenance therapy. 9 Although studies have shown that corticosteroids are effective in inducing remission in patients with active CD, 10 not all patients respond favorably. And among those patients that respond to induction corticosteroids, 40% to 68% of patients will relapse within a year, while up to 36% of patients will develop corticosteroid dependency.…”
Section: Non-biological Therapymentioning
confidence: 99%
“…8 However, de Franchis and coworkers showed that once patients achieved disease remission on mesalamine, less than 50% of patients were able to sustain disease remission after one year of maintenance therapy. 9 Although studies have shown that corticosteroids are effective in inducing remission in patients with active CD, 10 not all patients respond favorably. And among those patients that respond to induction corticosteroids, 40% to 68% of patients will relapse within a year, while up to 36% of patients will develop corticosteroid dependency.…”
Section: Non-biological Therapymentioning
confidence: 99%
“…Some clinical trials have suggested that mesalazine may be effective in certain subgroups of patients (eg, those in remission for only a short period of time), while others have shown that, overall, the treatment effect observed with mesalazine in patients with medically induced remission is minimal and not statistically significant (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). In patients who required glucocorticoids to control acute symptoms of Crohn's disease, mesalazine 4 g/day appeared to offer no therapeutic advantage over placebo (6).…”
Section: Mesalazine (5-aminosalicylates)mentioning
confidence: 99%
“…The time to relapse was 119 days for the mesalazine-treated patients compared with 109 days for placebo-treated patients (nonsignificant). In an Italian multicenter study, de Franchis et al [24] treated patients with Crohn’s disease having achieved remission on steroids either with 5-ASA 3 g daily or placebo, while steroids were doubled over 6 weeks. In this study, 5-ASA did not prevent relapse in Crohn’s disease patients (relapse rate after 20 months was 58% in the 5-ASA group and 52% in the placebo group).…”
Section: Treatmentmentioning
confidence: 99%